Keratin - Blumenberg, Miroslav (Biochemistry, 2018)
Keratin is the proteinaceous body covering layer produced by mammals, birds, fish, reptiles, and amphibians. Hair and wool, horns, claws, hooves, feathers, and scales are made of keratin. Keratin is insoluble in water and is resistant to proteolysis. Importantly, keratin is also the intracellular structural protein that protects living epithelial cells from mechanical damage or stress. The fundamental keratin functions are revealed in congenital human skin diseases caused by mutations in keratin genes, e.g., Epidermolysis bullosa simplex or Epidermolytic hyperkeratosis. Most keratin gene mutations have a dominant-negative effect disrupting the filamentous structure formation even from the natural allele, and leaving the cell with a deficient cytoskeleton. However, industrial scale meat production results in vast quantities of keratin byproduct. Processing this byproduct is, on the one hand a major challenge, and on the other hand, a potential for useful recycling and exploitation.